A Study of the Problem Based Learning Model with the Scaffolding Model as Independent Learning - Yusnidar Yusnidar; Haryanto Haryanto; Fuldiaratman Fuldiaratman; Sri Wina Oktavia; Sinta Marliya (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the Study: This study aims to investigate teachers’ perceptions of the application of the Problem-Based Learning model and the Scaffolding approach in supporting independent learning at Junior high school 1 Muaro Jambi. Understanding teacher responses is critical to optimizing instructional strategies aligned with the goals of the independent learning. Methodology: A descriptive quantitative research design was employed. The population consisted of all teachers at Junior high school 1 Muaro Jambi, with a sample of 19 respondents selected through a random sampling technique. Data were collected using validated questionnaires and analyzed using descriptive statistical methods to interpret the level of teacher response to both learning models. Main Findings: The results show that teachers expressed a positive response, with an average approval rating of 79.8% towards the implementation of both the Problem-Based Learning and Scaffolding models in promoting independent learning. Teachers acknowledged that these models enhanced student engagement, critical thinking skills, and autonomy in the learning process, although some highlighted the need for further training and resource support to maximize implementation. Novelty/Originality of this Study: This research offers a novelty contribution by providing empirical insights into teacher perceptions of combining PBL and Scaffolding approaches specifically within the framework of independent learning initiatives. Unlike previous studies that often focus solely on student outcomes, this study emphasizes the teacher’s role as a mediator in implementing innovative pedagogical models. The findings serve as a foundation for developing targeted professional development programs that empower teachers to foster more autonomous and student-centered classrooms.